Incorporation of acoustic sensors in the regulation of a mobile robot. (17th January 2019) - Luna-Aguilar, C. A.; Morales-Díaz, A. B.; Castelán, M.; Nadeu, C.
ABSTRACT: This article introduces the incorporation of acoustic sensors for the localization of a mobile robot. The robot is considered as a sound source and its position is located applying a Time Delay of Arrival (TDOA) method. Since the accuracy of this method varies with the microphone array, a navigation acoustic map that indicates the location errors is built. This map also provides the robot with navigation trajectories point-to-point and the control is capable to drive the robot through these trajectories to a desired configuration. The proposed localization method is thoroughly tested using both a 900 Hz square signal and the natural sound of the robot, which is driven near the desired point with an average error of 0.067 m. GRAPHICAL ABSTRACT: